Corrosion mechanism of cement-bonded Al2O3–MgAl2O4 pre-cast castables in contact with molten steel and slag. Issue 4 (15th February 2022) - Xiao, Junli; Chen, Junfeng; Li, Yuanyuan; Cheng, Yaping; Nath, Mithun; Zhang, Yu; Zheng, Lijun; Wei, Yaowu; Zhang, Shaowei; Li, Nan
Abstract: In this work, a cement-bonded corundum-spinel (Al2 O3 –MgAl2 O4 ) pre-cast refractory brick with two typical Al2 O3 aggregates was designed as the refractory lining. Corroded microstructure of the used corundum-spinel bricks after industrial trials in a commercial RH refining ladle was analyzed. Degradation processes of two types of alumina aggregates in the same corroded interface also were discussed. Typical corroded microstructure revealed that needle-like calcium hexaaluminate (CA6 ) was observed in the matrix of the original layer. The formation of CA6 was attributed to the reactions with pure calcium aluminate cement and matrix components under a high-temperature gradient during refining. Furthermore, the corrosion process of the used Al2 O3 –MgAl2 O4 bricks would be discussed based on a post-mortem microstructural characterization, and the corrosion mechanism of the two types of aggregates was also elucidated.